Serving up Data on Nutrient Composition of Aquatic Foods - Cohen, Philippa; Consalez, Fabio; Ahern, Molly; Masangwi, Sitilitha; Rittenschober, Doris; Holmes, Bridget; Kjellevold, Marian; Golden, Christopher; Hicks, Christina (WorldFish, 2022)
The nutrient values of fish and other aquatic foods can alleviate ‘hidden hunger’ or micronutrient deficiencies for many people in a range of geographies. But nutrient measures for many species, food types and geographies are unavailable, and are prohibitively expensive to measure. So, databases that house the data that do exist are incredibly valuable for health practitioners, fisheries managers, researchers and policy makers. There are many databases out there - each useful, overlapping and distinct in different ways. Here is a summary of these powerful databases the types of data they hold and how they compare.